Effects of TiO2 on the performance of silver coated on side-polished optical fiber for alcohol sensing applications - Kanmani, R.; Zainuddin, Nur Aina'a Mardhiah; Rusdi, Muhammad Farid Mohd; Harun, Sulaiman Wadi; Ahmed, Kawsar; Amiri, Iraj Sadegh; Zakaria, Rozalina (Elsevier, 2019)
This work reports the experimental and numerical investigations on the effect of titanium oxide (TiO2) integrated on the optical fiber silver (Ag) surface plasmon resonance (SPR) sensors. In this paper, the numerical simulation is also analyzed using the finite element method (FEM) which shows good agreement. Results are compared with the experimental findings, focusing on the SPR phenomena for refractive index sensing using side-polished optical fiber, where the characteristics of the Ag layer with the integration of TiO2 are optimized. The essential parameters include the thickness of Ag namely 20 nm, 30 nm and 40 nm for optimization studies of SPR properties. TiO2 was then coated on the Ag thin layer to sense isopropanol at different concentration. It is shown that the combination of a 30 nm thickness of Ag layer with a dielectric TiO2 improves sensor performance in terms of sensitivity reading of 268 nm/RIU with a detection limit of 0.012. The main interest is to develop the device with cost effective, ease fabrication and less cumbersome of sensors using TiO2 which one of an alternative material to defeat the oxidation process and avoid charge recombination. If the sensitivity increases at a higher wavelength, it indicates that the TiO2 holds great potential in photonic applications. © 2019 Elsevier Inc.